Physician workforce imbalances in Japan: how structural incentives shape hospital-based acute-care capacity - George Kujo (Human Resources for Health, 2026)
Abstract Japan's physician workforce problem in hospital-based high-intensity care is better understood as an interaction between distribution and retention than as a simple question of national physician headcount. This Comment examines three pathways that can reduce hospital service capacity: working conditions that impede entry and career continuity in high-intensity specialties; early movement from initial residency into cosmetic medicine, known as choku-bi; and later movement from hospital employment to clinic practice. Recent national data show substantial improvement in physician working hours after the 2024 Work Style Reform, but long hours remain concentrated in surgery, emergency medicine, and obstetrics and gynaecology. The national prevalence of choku-bi is not known; professional-society data instead provide a limited indicator of early entry into cosmetic practice. Published income data also show a large difference between salaried hospital practice and clinic ownership, but do not establish that income causes physicians to leave hospitals. These distinctions matter because national supply, specialty distribution, and movement across care settings are analytically different problems. Policy should therefore focus on measurable retention and distribution mechanisms: phasing out routine dependence on the highest service-related overtime ceilings, testing targeted retention incentives for high-intensity hospital functions, strengthening training and competency governance in cosmetic medicine, supporting career continuity, and collecting longitudinal data on physician transitions. Japan illustrates a broader workforce principle: adequate national headcount does not guarantee adequate service capacity when clinicians are difficult to distribute and retain in the settings where they are needed.